Effects of dopamine on leptin release and leptin gene (OB) expression in adipocytes from obese and hypertensive patients - Alvarez-Aguilar C; Alvarez-Paredes AR; Lindholm B; Stenvinkel P; García-López E; Mejía-Rodríguez O; López-Meza JE; Amato D; Paniagua R (International Journal of Nephrology and Renovascular Disease, 2013)
Cleto Alvarez-Aguilar,1–3 Alfonso Rafael Alvarez-Paredes,2 Bengt Lindholm,4 Peter Stenvinkel,4 Elvia García-López,4 Oliva Mejía-Rodríguez,5 Joel Edmundo López-Meza,6 Dante Amato,7 Ramon Paniagua8 1Hospital General Regional N°1, Instituto Mexicano del Seguro Social (IMSS), Morelia, 2Facultad de Ciencias Médicas y Biológicas "Dr. Ignacio Chávez" Universidad Michoacana de San Nicolás de Hidalgo (UMSNH), Morelia, Michoacán, 3División de Estudios Superiores, Universidad Nacional Autónoma de México (UNAM), México DF, México; 4Department of Clinical Science Intervention and Technology, Karolinska Institutet, Stockholm, Sweden; 5Coordinación Delegacional de Investigación en Salud, IMSS, Morelia, 6Centro Multidisciplinario de Estudios en Biotecnología (CMEB), UMSNH, Morelia, Michoacán, 7Facultad de Estudios Superiores Iztacala, UNAM, Tlalnepantla, 8Unidad de Investigación en Enfermedades Nefrológicas, Hospital de Especialidades, CMN Siglo XXI, IMSS, México DF, México Background: A reduction of dopaminergic (DAergic) activity with increased prolactin levels has been found in obese and hypertensive patients, suggesting its involvement as a pathophysiological mechanism promoting hypertension. Similarly, leptin action increasing sympathetic activity has been proposed to be involved in mechanisms of hypertension. The aim of this study was to analyze the effects of DA, norepinephrine (NE), and prolactin on leptin release and leptin gene (OB) expression in adipocytes from obese and hypertensive patients. Methods: Leptin release and OB gene expression were analyzed in cultured adipocytes from 16 obese and hypertensive patients treated with DA (0.001, 0.01, 0.1, and 1.0 µmol/L), NE (1.0 µmol/L), insulin (0.1 µmol/L), and prolactin (1.0 µmol/L), and from five nonobese and normotensive controls treated with DA (1 µmol/L), NE (1 µmol/L), insulin (0.1 µmol/L), and prolactin (1.0 µmol/L). Results: A dose-related reduction of leptin release and OB gene messenger ribonucleic acid expression under different doses of DA was observed in adipocytes from obese hypertensive patients. Whereas prolactin treatment elicited a significant increase of both leptin release and OB gene expression, NE reduced these parameters. Although similar effects of DA and NE were observed in adipocytes from controls, baseline values in controls were reduced to 20% of the value in adipocytes from obese hypertensive patients. Conclusion: These results suggest that DAergic deficiency contributes to metabolic disorders linked to hyperleptinemia in obese and hypertensive patients. Keywords: dopamine, leptin, cultured adipocytes, obesity, hypertension